Reproducibility and Daytime-Dependent Changes of Corneal Epithelial Thickness and Whole Corneal Thickness Measured With Fourier Domain Optical Coherence Tomography. Issue 3 (March 2016) - Wasielica-Poslednik, Joanna; Lisch, Walter; Bell, Katharina; Weyer, Veronika; Pfeiffer, Norbert; Gericke, Adrian
Abstract : Purpose: To evaluate the reproducibility of Fourier domain anterior segment optical coherence tomography (RTVue) based on repeated measurements of corneal thickness (CT) and epithelial thickness (ET) and to test daytime-dependent changes of these parameters. Methods: Twenty-three eyes from 23 healthy volunteers were included in this prospective study. Three clinical observers performed 3 consecutive measurements each of CT and ET in 3 sessions using RTVue, resulting in 9 measurements per session. Session 1 was performed at 9 AM ± 1 hour, session 2 at 4 PM ± 1 hour on the same day, and session 3 at 9 AM ± 1 hour 2 days later. CT and ET were assessed in 9 areas: corneal vertex, 4 paracentral zones, and 4 peripheral zones. Results: The mean intraclass correlations (ICCs) for intraobserver and interobserver reproducibility were almost perfect (0.81–0.99) for CT in all corneal zones and for ET in all but 2 peripheral zones. Intraobserver ICC was substantial (0.61–0.8) for superior peripheral area and interobserver ICC for superior and inferior peripheral positions. CT and ET decreased significantly from morning to afternoon sessions [−3.15 μm ( P < 0.0001) and −0.52 μm ( P < 0.0001), respectively]. ET correlated weakly to moderately with CT. Conclusions: RTVue yields almost perfect reproducibility for CT and ET in central, paracentral, and peripheral lateral zones. Central CT and ET were significantly thinner in the afternoon compared with the morning.